Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia - Gagarin, Vladimir G.; Naumova, Tatyana V. (Zootaxa, 2016)
Two new nematode species found in Lake Baikal (Russia) are described and illustrated. Tobrilus methanus sp. n. is morphologically close to T. modestus Gagarin, 1996 and T. incognitus Tsalolikhin, 1972. The new species differs from T. modestus by the thinner body (a = 20–29 vs a = 15.5–18.5), longer pharynx (b = 3.4–4.4 vs b = 5.0–6.2), comparatively longer tail (cʹ = 3.4–5.0 vs cʹ = 2.0–2.5), less number of supplementary organs (6 vs 7–8) and presence of subterminal seta. T. methanus sp. n. differs from T. incognitus by the thicker body (a = 20–29 vs a = 35–37), longer pharynx (b = 3.4–4.4 vs b = 5.1–5.8), shorter outer labial setae (3–4 µm long vs 10 µm long) and presence of crystalloids. Tripyla posolskii sp. n. is close to T. dybowskii Tsalolikhin, 1976, but differs by the shorter body (L = 1548–2078 µm vs L = 2400–3530 µm), shorter tail (c = 4.7–7.2, cʹ = 5.8–7.9 vs c = 2.8–4.8, cʹ = 7.3–11.9) and shorter spicules (47–57 µm long vs 85–92 µm long). A key for the identification of valid species of the genus Tobrilus from Lake Baikal is given.